Bubbles Coalescence Frequency and Transition Concentration in Bubble Column - Fadi Z. Hanna; Ihsan B. Hamawand (Tikrit Journal of Engineering Sciences, 2006)
Bubbles coalescence frequency and the transition concentration in a dispersion column were studied experimentally by using ethanol-water mixture as a liquid phase and air as a gas phase. The study was devoted to express the effect of the liquid properties on the performance of the dispersion column, and the experimental work was designed for this purpose, where the range of weight percent of ethanol in water, (0.1-0.7) Wt%, and the range of superficial gas velocity of air, (2.5-30) mm/s. The experimental runs were planned using the central composite routable design method. The experimental data obtained agreed quite well with a polynomial type of correlations by using computer program. The experimental data shows that the values of bubble coalescence decrease with increasing superficial gas velocity of air, and ethanol transition concentration was successfully correlated as a function of the superficial gas velocity of air,